(untitled) (Journal of the College of Education for Women, 2022)
The research deals with the problem of visual pollution, as it is one of the most important urban problems that cities suffer from. The concept of visual pollution has recently emerged to describe the deformation and degradation of the urban environment. Visual pollution is defined as any component of the surrounding environment that is inconsistent and not homogeneous with its natural and human components. The volume of visual pollution has doubled due to the non-compliance with the laws, regulations and controls set by the Municipality of Baghdad by the citizens, and to the weak municipal role that the municipality plays in implementing these laws. Therefore, it has become necessary to know the manifestations of visual pollution and their geographical distribution, and the variations between the neighborhoods of the Shuala. The research has adopted the field work to document the manifestations of visual pollution through photography. It has further involved using a questionnaire that was distributed on a random stratified sample of (400 questionnaires) distributed among the four districts of Al-Shula, Al-Hurriya, Al-Harbiya, and Al-Abbasiya). The number of questionnaires for each neighborhood reached (100 questionnaires), to find out the various manifestations of visual pollution within the neighborhoods of Al-Shula. The spread of the manifestations of visual pollution in the municipality of Al-Shula is considered part of the daily life of the citizens. It has also found that some variables have effectively contributed to the spread of the phenomenon of visual pollution through the division of heterogeneous residential units and heights of the non-buildings. Moreover, there have been signs of harmonization and the exploitation of balconies in a non-civilized manner and asymmetry of the urban fabric of Al-Shula.